2018
DOI: 10.1002/ijc.31543
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior cancer history on the overall survival of patients newly diagnosed with cancer: A pan‐cancer analysis of the SEER database

Abstract: The population of cancer survivors with prior cancer is rapidly growing. Whether a prior cancer diagnosis interferes with outcome is unknown. We conducted a pan-cancer analysis to determine the impact of prior cancer history for patients newly diagnosed with cancer. We identified 20 types of primary solid tumors between 2004 and 2008 in the Surveillance, Epidemiology, and End Results database. Demographic and clinicopathologic variables were compared by χ test and t-test as appropriate. The propensity score-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 15 publications
10
77
1
Order By: Relevance
“…21,22 The results of this study indicate that the increase in cancer-specific mortality is likely attributable to a combination of both an increase in the incidence of SPMs 3 and poorer relative survival after an SPM diagnosis. 26,27 Keegan et al 27 evaluated differences in survival by age at SPM and observed that the 5-year OS rate was 33% lower for individuals diagnosed with an SPM at an age <15 years, 20% lower for individuals diagnosed with an SPM at an age of 15 to 39 years, and 8% lower for individuals diagnosed with an SPM at an age ≥40 years. Disparities in OS were observed for survivors of childhood cancer independently of demographic factors, the age at the childhood cancer diagnosis, the time from childhood cancer to the SPM diagnosis, and exposure to radiotherapy during childhood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 The results of this study indicate that the increase in cancer-specific mortality is likely attributable to a combination of both an increase in the incidence of SPMs 3 and poorer relative survival after an SPM diagnosis. 26,27 Keegan et al 27 evaluated differences in survival by age at SPM and observed that the 5-year OS rate was 33% lower for individuals diagnosed with an SPM at an age <15 years, 20% lower for individuals diagnosed with an SPM at an age of 15 to 39 years, and 8% lower for individuals diagnosed with an SPM at an age ≥40 years. Disparities in OS were observed for survivors of childhood cancer independently of demographic factors, the age at the childhood cancer diagnosis, the time from childhood cancer to the SPM diagnosis, and exposure to radiotherapy during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the impact of a prior cancer history on subsequent cancer outcomes among adults with prostate, lung, or gastrointestinal cancers. [23][24][25] Zhou et al 26 recently explored whether a history of any prior cancer adversely influenced survival across 20 adult cancer sites. Although the HRs were attenuated in comparison with those observed in the current study, a history of prior cancer was associated with inferior outcomes for secondary breast cancer (HR, 1.27; 95% CI, 1.24-1.30), melanoma (HR, 1.23; 95% CI, 1.19-1.27), bone and soft-tissue sarcoma (HR, 1.17; 95% CI, 1.09-1.25), and thyroid cancer (HR, 1.56; 95% CI, 1.43-1.69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has mentioned the different impact of prior cancer according to the specific cancer (8). We creatively divided these cancers into two categories, "prior cancer inferior" (PCI), in which patients had lower survival rates than those without prior cancer; and "prior cancer similar" (PCS), in which survival rates were similar.…”
Section: Discussionmentioning
confidence: 99%
“…This practice is mainly based on the long-held assumption that prior cancer diagnosis and treatment could interfere with study outcomes. However, our previous pan-cancer study suggested that not all prior cancers actually interfere with study outcomes (8). The number of cancer survivors has a 4-fold increase in the United States over the last three decades (9).…”
Section: Introductionmentioning
confidence: 97%